Pemeliharaan Sarana Prasarana di SMK Negeri 2 Palembang - Amilda, Amilda; Apriliyanti, Eka; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the maintenance of facilities and infrastructure at SMK Negeri 2 Palembang, focusing on planning activities for facilities and infrastructure, conducting routine maintenance, emergency maintenance, and preventive maintenance. This research uses a descriptive qualitative approach with a qualitative research design. Data collection techniques include interviews, observation, and documentation. Data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. The findings indicate that the maintenance of facilities and infrastructure at SMK Negeri 2 Palembang has been carried out effectively. The maintenance process encompasses several key indicators, including planning activities for facilities and infrastructure, conducting routine maintenance, performing emergency maintenance, and carrying out preventive maintenance. Based on the results, the author concludes that the maintenance of facilities and infrastructure at SMK Negeri 2 Palembang has been implemented very well, supported by proper planning, routine maintenance, emergency repairs, and preventive measures